Interpretive Policy of the Supreme Court of Pakistan: A Critical Analysis from the Perspective of Islamic Interpretive System (Journal of Asian Development Studies, 2013)
The present article provides an analysis of the interpretive policy of the Supreme Court of Pakistan from the perspective of Islamic interpretive system. For a long time and particularly after the insertion of “Objective Resolution” as a substantive part of Article 2-A of the Constitution of Pakistan 1973, the Supreme Court of Pakistan often claims as having capacity of an independent mujtahid. In this context, this article provides that in majority of the cases, the Supreme Court of Pakistan does not perform ijtihād rather follows the principles of amalgamation and selection (takhyyīr and talfīq) and as well as foreign methods of interpretation. This paper concludes that constitutionally, Supreme Court of Pakistan have authority to do independent ijtihād but is not exercising ijtihād rather working on ad hoc basis by following any of the juristic opinions or by adopting Western rules. This article suggests that the Court should review its interpretive policy in the light of the Islamic techniques of interpretation. It invites the Court to do ijtihād rather than following the principles of takhyyīr and talfīq or foreign methods. It also invites the Court to establish a general policy of interpretation by following the unique interpretive principles of the Qur’ān and the Sunnah such as contextual interpretation, public interest, purposive interpretation and rule of customs etc. The literal rule, the golden rule and the mischief rule have no worth if compared with the contextual rule, rule of maslaḥah mursalah/public interest and ijtihād al-maqāṣid of Islamic interpretive system.